Evaluation of viscosity and pH of Zingiber officinale var. officinale juice in mouthwash formulation - Stefani, Rosita; Vanessa, Gisela Ellenia; Fibryanto, Eko (Majalah Kedokteran Gigi Indonesia, 2023)
Zingiber officinale var. officinale juice has many benefits, including as a mixture of mouthwash. This research aims to analyze the differences in pH and viscosity values of Zingiber officinale var. officinale-containing mouthwashes with concentrations of 3.125%, 6.25%, and 12.5% on days 0, 14, 28, 42, and 56. Zingiber officinale var. officinale-containing mouthwashes with concentrations of 3.125%, 6.25%, and 12.5% were mixed with propylene glycol, PEG-40 hydrogenated castor oil, oleum menthae, benzoic acid, sodium benzoate, calcium lactate, sorbitol 70% and calcium thiocyanate. The formulation was measured with a pH meter (Jenway, United Kingdom) and a viscometer (Brookfield, Massachusetts) for 56 days. pH data was analyzed using GLM repeated measures ANOVA and one-way ANOVA (p < 0.05). Viscosity data was analyzed using GLM repeated measured ANOVA and the Kruskal-Wallis test (p < 0.05). The pH value of the 3.125% formulation showed significant difference for 56 days in the range of 5.50-5.61. The viscosity value showed no significant difference for 56 days in the range of 3.03-3.09 cP. The pH and viscosity value of the 6.25% formulation showed no significant difference for 56 days with pHs of 5.78-5.83, while the viscosity is 3.12-3.13 cP. The pH and viscosity value of the 12.5% formulation showed no significant difference for 56 days with pHs of 4.90, while the viscosity was 3.43-3.50 cP. The Zingiber officinale var. Officinale mouthwash formulation with a concentration of 3.125% was unstable, but it had the lowest viscosity value and was stable for 56 days. The pH and viscosity value of the 6.25% and 12.5% formulations were stable for 56 days. The highest pH value was in the 6.25% formulation.